KAJIAN BENTUK, MAKNA DAN FUNGSI KEWANGEN SEBAGAI PRODUK BUDAYA KEAGAMAAN - Ni Wayan Murniti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
There are some materials needed for the Balinese especially Hindu to do their activities or yadnya ceremony. Can not be mentioned the difficulties of variety in each of their meaning and function. Although there is a simple one but it still has their own importance of meaning and function. One example of the materials is called Kewangen. Why Kewangen still exists and how far the comprehensions of The Hindus about the materials of their yadnya are the questions needed to be discussed. For the overall purposes, this study is presented contextually which isable to describe three importance things which contained their problems and purposes, such as: 1). Is Kewangen categorized as the product of culture, 2). What is the Kewangen looks like, 3) What is the meaning and function of Kewangen from the Hindus perceptions.